Rotational angles and velocities during down the line and diagonal across court volleyball spikes - Brown, J. R.; Alsarraf, B. J.; Waller, M.; Eisenman, P.; Hicks-Little, C. A. (International Journal of Kinesiology & Sports Science, 2014)
The volleyball spike is an explosive movement that is frequently used to end a rally and earn a point. High velocity spikes are an important skill for a successful volleyball offense. Although the influence of vertical jump height and arm velocity on spiked ball velocity (SBV) have been investigated, little is known about the relationship of shoulder and hip angular kinematics with SBV. Other sport skills, like the baseball pitch share similar movement patterns and suggest trunk rotation is important for such movements. The purpose of this study was to examine the relationship of both shoulder and hip angular kinematics with ball velocity during the volleyball spike. Methods: Fourteen Division I collegiate female volleyball players executed down the line (DL) and diagonally across-court (DAC) spikes in a laboratory setting to measure shoulder and hip angular kinematics and velocities. Each spike was analyzed using a 10 Camera Raptor-E Digital Real Time Camera System. Results: DL SBV was significantly greater than for DAC, respectively (17.54±2.35 vs. 15.97±2.36 m/s, p<0.05). The Shoulder Hip Separation Angle (S-HSA), Shoulder Angular Velocity (SAV), and Hip Angular Velocity (HAV) were all significantly correlated with DAC SBV. S-HSA was the most significant predictor of DAC SBV as determined by regression analysis. Conclusions: This study provides support for a relationship between a greater S-HSA and SBV. Future research should continue to 1) examine the influence of core training exercise and rotational skill drills on SBV and 2) examine trunk angular velocities during various types of spikes during play.